Social perception in synaesthesia for colour. Issue 7 (16th November 2016) - Janik McErlean, Agnieszka B.; Susilo, Tirta; Rezlescu, Constantin; Bray, Amy; Banissy, Michael J.
ABSTRACT: Synaesthesia is a rare phenomenon in which stimulation in one modality (e.g., audition) evokes a secondary percept not associated with the first (e.g., colour). Prior work has suggested links between synaesthesia and other neurodevelopmental conditions that are linked to altered social perception abilities. With this in mind, here we sought to examine social perception abilities in grapheme–colour synaesthesia (where achromatic graphemes evoke colour experiences) by examining facial identity and facial emotion perception in synaesthetes and controls. Our results indicate that individuals who experience grapheme–colour synaesthesia outperformed controls on tasks involving fine visual discrimination of facial identity and emotion, but not on tasks involving holistic face processing. These findings are discussed in the context of broader perceptual and cognitive traits previously associated with synaesthesia for colour, with the suggestion that performance benefits shown by grapheme–colour synaesthetes may be related to domain-general visual discrimination biases observed in this group.